An experience of virtual leadership development for human resource managers - Johnson Sarah; Nauseda Fiona; Sherk Karen E; Liston Delphine (BMC, 2009)
Abstract Problem Strong leadership and management skills are crucial to finding solutions to the human resource crisis in health. Health professionals and human resource (HR) managers worldwide who are in charge of addressing HR challenges in health systems often lack formal education in leadership and management. Approach Management Sciences for Health (MSH) developed the Virtual Leadership Development Program (VLDP) with support from the United States Agency for International Development (USAID). The VLDP is a Web-based leadership development programme that combines face-to-face and distance-learning methodologies to strengthen the capacity of teams to identify and address health challenges and produce results. Relevant changes The USAID-funded Leadership, Management and Sustainability (LMS) Program, implemented by MSH, and the USAID-funded Capacity Project, implemented by IntraHealth, adapted the VLDP for HR managers to help them identify and address HR challenges that ministries of health, other public-sector organizations and nongovernmental organizations are facing. Local settings Three examples illustrate the results of the VLDP for teams of HR managers: 1. the Uganda Protestant and Catholic Medical Bureaus 2. the Christian Health Association of Malawi 3. the Developing Human Resources for Health Project in Uganda. Lessons learnt The VLDP is an effective programme for developing the management and leadership capacity of HR managers in health.